determine determine whether the following geometric series converges or diverges. if the series converges find its sum.

plz help me​

determine determine whether the following geometric series converges or diverges if the series converges find its sumplz help me class=

Respuesta :

For starters,

[tex]\dfrac{3^k}{4^{k+2}}=\dfrac{3^k}{4^24^k}=\dfrac1{16}\left(\dfrac34\right)^k[/tex]

Consider the [tex]n[/tex]th partial sum, denoted by [tex]S_n[/tex]:

[tex]S_n=\dfrac1{16}\left(\dfrac34\right)+\dfrac1{16}\left(\dfrac34\right)^2+\dfrac1{16}\left(\dfrac34\right)^3+\cdots+\dfrac1{16}\left(\dfrac34\right)^n[/tex]

Multiply both sides by [tex]\frac34[/tex]:

[tex]\dfrac34S_n=\dfrac1{16}\left(\dfrac34\right)^2+\dfrac1{16}\left(\dfrac34\right)^3+\dfrac1{16}\left(\dfrac34\right)^4+\cdots+\dfrac1{16}\left(\dfrac34\right)^{n+1}[/tex]

Subtract [tex]S_n[/tex] from this:

[tex]\dfrac34S_n-S_n=\dfrac1{16}\left(\dfrac34\right)^{n+1}-\dfrac1{16}\left(\dfrac34\right)[/tex]

Solve for [tex]S_n[/tex]:

[tex]-\dfrac14S_n=\dfrac3{64}\left(\left(\dfrac34\right)^n-1\right)[/tex]

[tex]S_n=\dfrac3{16}\left(1-\left(\dfrac34\right)^n\right)[/tex]

Now as [tex]n\to\infty[/tex], the exponential term will converge to 0, since [tex]r^n\to0[/tex] if [tex]0<r<1[/tex]. This leaves us with

[tex]\displaystyle\lim_{n\to\infty}S_n=\lim_{n\to\infty}\sum_{k=1}^n\frac{3^k}{4^{k+2}}=\sum_{k=1}^\infty\frac{3^k}{4^{k+2}}=\frac3{16}[/tex]

Answer:

3/16 (converges)

Step-by-step explanation:

Let's write out the first few terms of this sequence, from k=1 to k=3. This gives us:

sum = (3^1)/(4^(1+2)) + (3^2)/(4^(2+2)) + (3^3)/(4^(3+2)) + ...

Computing that into numbers, we have:

sum = 3/64 + 9/256 + 27/1024 + ...

Now, what happens if we multiply both sides by 4/3 (which we get from the 3 and the 4 in the problem)? This gives us:

(4/3)*sum = 4/3*(3/64) + 4/3*(9/256) + 4/3*(27/1024) + ...

which computes out to:

(4/3)*sum = 1/16 + 3/64 + 9/256 + ...

Now, if we subtract sum from 4/3*(sum), notice that most of the terms cancel out. We are left with:

(4/3)*sum - sum = 1/16

Solving this algebraic equation gives us sum = 3/16